Stem Cells as Therapy for Necrotizing Enterocolitis: A Systematic Review and Meta-Analysis of Preclinical Studies - Villamor-Martinez, Eduardo; Hundscheid, Tamara; Kramer, Boris W.; Hooijmans, Carlijn R; Villamor, Eduardo (Frontiers in Pediatrics, 2020)
Background: Necrotizing enterocolitis (NEC) is the most common life-threatening gastrointestinal condition among very and extremely preterm infants. Stem cell therapy has shown some promising protective effects in animal models of intestinal injury, including NEC, but no systematic review has yet evaluated the preclinical evidence of stem cell therapy for NEC prevention or treatment. Methods: PubMed and EMBASE databases were searched for studies using an animal model of NEC with stem cells or their products. The SYRCLE tool was used for the assessment of risk of bias. A random-effects model was used to pool odds ratios (OR) and 95% confidence interval (CI). Results: We screened 953 studies, of which 9 (8 rat, 1 mouse model) met the inclusion criteria. All animal models induced NEC by a combination of hypothermia, hypoxia and formula feeding. Risk of bias was evaluated as unclear on most items for all studies included. Meta-analysis found that both mesenchymal and neural stem cells and stem cell-derived exosomes reduced the incidence of all NEC (OR 0.22, 95% CI 0.16-0.32, k=16), grade 2 NEC (OR 0.41, 95% CI 0.24-0.70, k=16), and grade 3-4 NEC (OR 0.28, 95% CI 0.19-0.42, k=16). K represents the number of independent effect sizes included in each meta-analysis. The effect of the exosomes was similar to that of the stem cells. Stem cells and exosomes also improved 4-day survival (OR 2.89 95% CI 2.07-4.04, k=9), and 7-day survival (OR 3.96 95% CI 2.39-6.55, k=5) after experimental NEC. Meta-analysis also found that stem cells reduced other indicators of intestinal injury. Conclusion: The data from this meta-analysis suggest that both stem cells and stem cell-derived exosomes prevented NEC in rodent experimental models. However, unclear risk of bias and incomplete reporting underline that poor reporting standards are common and hamper the reliable interpretation of preclinical evidence for stem cell therapy for NEC.